The Role of Indian Caste Identity and Caste Inconsistent Norms on Status Representation - Sankaran, Sindhuja; Sekerdej, Maciek; von Hecker, Ulrich (Frontiers in Psychology, 2017)
The Indian caste system is a complex social structure wherein social roles like one’s profession became ‘hereditary’, resulting in restricted social mobility and fixed status hierarchies. Furthermore, we argue that the inherent property of caste heightens group identification with one’s caste. Highly identified group members would protect the identity of the group in situations when group norms are violated. In this paper, we were interested in examining the consequence of caste norm violation and how an individual’s status is mentally represented. High caste norms are associated with moral values while the lower caste norms are associated with immorality. We predicted a ‘black sheep effect’, that is, when high caste individuals’ group identity (caste norm violation condition) is threatened their salient high caste identity would increase, thereby resulting in devaluing the status of their fellow in-group member if the latter is perceived as perpetrator. We presented participants with a social conflict situation of a victim and a perpetrator that is ‘Caste norm consistent’ (Lower caste individual as a perpetrator and higher caste individual as a victim) and vice versa ‘Caste norm inconsistent’ condition (higher caste individual as perpetrator and lower caste individual as a victim). Then, participants had to choose from nine pictorial depictions representing the protagonists in the story on a vertical line, with varying degrees of status distance. Results showed evidence for the black sheep effect and, furthermore, revealed that no other identity (religious, national, regional) resulted in devaluing the status of fellow in-group member. These results help us understand the ‘black sheep ‘effect in the context of moral norms and status representation and are discussed in the framework of the Indian society.